Analisis Kesalahan Penulisan Teks Surat Dinas: Studi Kasus pada Peserta Didik Kelas VII B MTs Negeri 2 Banyumas - Indriyati, Sri; Kuntoro (Proceedings Series on Social Sciences & Humanities, 2024)
This study aims to describe the types of errors made by seventh-grade students in class VII B of MTs Negeri 2 Banyumas in writing official letters. The errors discussed include spelling, word choice (diction), structural cohesion, capitalization errors, and difficulties in using standardized words in writing official letters. This study uses a qualitative descriptive method with a focus on a case study. The data used are official letters written by the students, which are analyzed, classified, and evaluated to assess the errors that occurred. The findings indicate that the errors that occurred included the use of capital letters, conjunctions, prepositions, and punctuation marks; inadequate word choice; difficulties in using standardized words; and ineffective sentence structure. These errors can affect the effectiveness of official letters in conveying the intended ideas. Therefore, specific teaching and training are needed to address these errors and improve the writing skills of students in writing official letters.